The Effect of Obesity, Bariatric Surgery, and Operative Time on Abdominal Body Contouring Outcomes. (8th March 2021) - Vasilakis, Vasileios; Lisiecki, Jeffrey L; Kortesis, Bill G; Bharti, Gaurav; Hunstad, Joseph P
Abstract: Background: Abdominal body contouring procedures are associated with the highest rates of complications among all aesthetic procedures. Patient selection and optimization of surgical variables are crucial in reducing morbidity and complications. Objectives: The purpose of this single-institution study was to assess complication rates, and to evaluate BMI, operative time, and history of bariatric surgery as individual risk factors in abdominal body contouring surgery. Methods: A retrospective chart review was performed of all patients who underwent abdominoplasty, circumferential lower body lift, fleur-de-lis panniculectomy (FDL), and circumferential FDL between August 2014 and February 2020. Endpoints were the incidence of venous thromboembolism, bleeding events, seroma, infection, wound complications, and reoperations. Univariate statistical analysis and multivariate logistic regressions were performed. Covariates in the multivariate logistic regression were BMI, procedure time, and history of bariatric surgery. Results: A total of 632 patients were included in the study. Univariate analysis revealed that longer procedure time was associated with infection ( P  = 0.0008), seroma ( P  = 0.002), necrosis/dehiscence ( P  = 0.01), and reoperation ( P  = 0.002). These associations persisted following multivariate analyses. There was a trend toward history of bariatric surgery being associated with minor reoperation ( P  = 0.054). No significant increase in the incidence of major reoperation was found in association with overweight or obese patient habitus, history of bariatric surgery, or prolonged procedure time. BMI was not found to be an individual risk factor for morbidity in this patient population. Conclusions: In abdominal body contouring surgery, surgery lasting longer than 6 hours is associated with higher incidence of seroma and infectious complications, as well as higher rates of minor reoperation. Level of Evidence: 4: